Ultrafast all-optical ALU operation using a soliton control within the cascaded InGaAsP/InP microring circuits - Soysouvanh, S.; Phongsanam, P.; Mitatha, S.; Ali, J.; Yupapin, P.; Amiri, I. S.; Grattan, K. T.V.; Yoshida, M. (My University, 2019)
A dark-bright soliton conversion is used to perform the two arithmetic logic unit operations namely adder and subtractor operations. The advantage of the system such as power stability, non-dispersion and the dark-bright soliton phase conversion control can be obtained. The input source into the circuit is the bright soliton pulse, with the pulse width of 35 ps, the peak power at 1.55 µm is 1 mW. By using the dark-bright soliton conversion pair, the generated logic bits can be controlled, and the secure bits can be achieved. The simulation results show the output signal with a minimum loss of only 0.1% with respect to a low input power of 1 mW, and ultra-fast response time of about 1 ps can be achieved. It gives the ultra-high bandwidth of more than 40 Gbits−1. The circuit composes six microring resonators made of InGaAsP/InP material with smaller ring radii of 1.5 µm, and the total physical scale of the circuit less than 100 µm2.